THE ROLE OF INTERNAL AUDIT IN ACTIVATING CORPORATE GOVERNANCE: EVIDENCE FROM IRAQ - Mustafa Hassan Malak; Hayder J. Ahmed Al- Gburi; Nahla. u. Talal Alshammari (Scholar Express Journals, 2025)
Internal Auditing: Closed System Perspective ABSTRACT: The study seeks to show the importance and effectiveness of the internal audit that serve parties in corporate governance, including the audit committee, external auditors, as well as the board of directors. Consequently, all internal audit the Institute of Internal Auditors standards have grown to be one of the best weapons to ensure the quality of audit procedures and thus making value to companies through services offered, such as regulatory consulting, assurance services, risk assessment, verification of procedures and tests of compliance with transparency and disclosure standards. All these are bounded by corporate governance. In order to satisfy the research objectives,A descriptive analysis of the suitability of such analyses/models for studies of this kind and the principle of gathering data at the source. Data collection was carried out using a prepared questionnaire by sending out 85 electronic questionnaires to a sample that enabled statistical analyses,The given sentence has been broken into multiple sentences for readability Iraqi Commercial Banks a random of employees Once analysis was done with the Statistical Package for the Social Sciences (SPSS-23), the results of the practical research showed a statistically significant positive effect at the significance level of 0.05 for all variables. The research concluded that internal audit has a significant impact on the application of governance principles in Iraqi commercial banks. The internal control systems in these banks contribute to monitoring the operations of the banks through continuous disclosure of risks. It is also essential to support the independence of internal audit in Iraqi commercial banks to provide more credible results, along with continuous supervision of the importance of supporting internal audit systems through seminars and training courses to keep pace with modern technological developments and enable all auditors to keep up with modern international standards.
Keywords: Corporate Governance; internal audit; Internal audit objectives